2011
DOI: 10.1007/s10653-011-9428-9
|View full text |Cite
|
Sign up to set email alerts
|

Uranium in vegetable foodstuffs: should residents near the Cunha Baixa uranium mine site (Central Northern Portugal) be concerned?

Abstract: Large uranium accumulations in vegetable foodstuffs may present risks of human health if they are consumed. The objective of this study was to evaluate the uranium concentrations in different vegetable foodstuffs and grown in agricultural soils, which are then consumed by the residents of the village of Cunha Baixa (Portugal),--located in an former uranium mining area. This study was conducted to address concerns expressed by the local farmers as well as to provide data for uranium-related health risk assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Agricultural phosphate fertilization also accounts for a major source of U dissemination (Schipper et al ., ; Wetterlind et al ., ). In its soluble form, U may be taken up by plants and can therefore contaminate the food chain (Neves et al ., ). Uranium is a chemotoxic and radiotoxic element.…”
Section: Introductionmentioning
confidence: 97%
“…Agricultural phosphate fertilization also accounts for a major source of U dissemination (Schipper et al ., ; Wetterlind et al ., ). In its soluble form, U may be taken up by plants and can therefore contaminate the food chain (Neves et al ., ). Uranium is a chemotoxic and radiotoxic element.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, higher uranium concentrations are found in plants, especially leafy plants, in the immediate vicinity of uranium waste dumps compared to control areas [35]. Uranium concentrations evaluated in foodstuffs grown in agricultural soils located in former uranium mining areas also show high uranium concentrations in irrigation waters and some vegetables, including lettuce, potato, green bean pods and cabbage [36]. These findings suggest that residents of certain areas, namely those in regions surrounding granite-weathering soils, uranium waste dumps and former uranium mining areas, are at higher risk of environmental uranium exposure.…”
Section: Discussionmentioning
confidence: 93%
“…Uranium is another geogenic, potentially toxic contaminant [192] and studies in nutrient culture show its uptake by crops [193,194]. Several studies confirmed that irrigation water contaminated with uranium has an impact on crop quality though less to soil contamination by uranium [195][196][197]. Lead, mercury [38], chromium [198] and cadmium [199] are also known to accumulate in crops grown on soils with high levels of these contaminants.…”
Section: Geogenic Contaminants In Irrigation Watermentioning
confidence: 99%
“…While there is extensive information in the literature on uptake by plants, most studies have focused on the general type of contaminant, or its accumulation in crops, use in phytoremediation of soils and the pathway of uptake within the crop. Contaminated irrigation water is capable of enriching surface soil with these contaminants [200] and likely enhances availability for uptake by crops [197]. There are few federal guidelines for trace element limits in foods in the United States, other than in arsenic, lead, cadmium, and mercury in wastewater [201], and the evidence suggests there is an urgent need for irrigation water quality standards that include geogenic contaminants.…”
Section: Geogenic Contaminants In Irrigation Watermentioning
confidence: 99%